The Concept of ‘Water’ in the Metaphorics of Economic Discourse - Davidko, Natalya (Verbum, 2012)
Cognitive onomasiology opens up new avenues for studying the processes of linguistic denomination of concepts. Economics as science and business as we know it today are more recent developments of human thought and activity than philosophy, or mathematics, or various trades, that is why they have to draw on general literary language or other sciences for their terms, hence the abundance of metaphorical designations in their terminological systems. Traditional studies within the framework of the Conceptual Metaphor Theory proceed from the target concept and aim to expose the systematicity of meaningful mappings with various source domains. The current research differs from them in that it proceeds from the source domain: the point of departure is the concept of WATER as an entity separate from the word ‘water’. The concept is treated as a unit of cognition constructed in the course of cognizance of a multitude of characteristics (components) which constitute the intension of the concept. The main aim of this research is to expose cognitively salient conceptual components of WATER which are operative in metaphorical designations and in the formation of conceptual content of newly formed economics and business terms (e.g. liquidity, flow, etc.).